2021
DOI: 10.3390/w13121640
|View full text |Cite
|
Sign up to set email alerts
|

Sediment and Nutrient Retention in Ponds on an Agricultural Stream: Evaluating Effectiveness for Diffuse Pollution Mitigation

Abstract: The creation of ponds and wetlands has the potential to alleviate stream water quality impairment in catchments affected by diffuse agricultural pollution. Understanding the hydrological and biogeochemical functioning of these features is important in determining their effectiveness at mitigating pollution. This study investigated sediment and nutrient retention in three connected (on-line) ponds on a lowland headwater stream by sampling inflowing and outflowing concentrations during base and storm flows. Sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…There was a significant decrease in BOD and phosphate levels before and after dredging in Lunawa Lagoon, which could be due to the removal of organic sediments with dredged materials (Perera and De Alwis 2011). According to Pettersson (1998) and Robotham et al, (2021), fine-grain sediment consists of high concentrations of soluble nitrogen and phosphorus. Phosphates levels could be increased as a result of excessive fertilization loaded in the reservoir that is discharged to the water body from the agricultural canals.…”
Section: Resultsmentioning
confidence: 98%
“…There was a significant decrease in BOD and phosphate levels before and after dredging in Lunawa Lagoon, which could be due to the removal of organic sediments with dredged materials (Perera and De Alwis 2011). According to Pettersson (1998) and Robotham et al, (2021), fine-grain sediment consists of high concentrations of soluble nitrogen and phosphorus. Phosphates levels could be increased as a result of excessive fertilization loaded in the reservoir that is discharged to the water body from the agricultural canals.…”
Section: Resultsmentioning
confidence: 98%
“…P10_US_OLP had an exceptionally high rate compared to other online features because it is the most upstream feature in a series of three connected features. Robotham et al (2021) showed that P10_US_OLP was generally the most effective at trapping sediment. Therefore, where NBS interventions are placed in series, features that are located farthest upstream are likely to require more frequent maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The studied features were constructed between February 2018 and February 2019 and vary in their design and hydrology (Table 1). Further details on the Littlestock Brook NFM trial are given by Old et al (2019) and Robotham et al (2021).…”
Section: Methodology and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the increasing soil erosion by intensified agricultural practices and associated N and P contaminants lead to environmental and water pollution (Robotham et al, 2021;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%